Leisure-time exercise is associated with lower depressive symptoms in community dwelling adults - Aguilar, Beatriz A. S. [UNESP]; Tebar, William R. [UNESP]; Silva, Stefany C. B. [UNESP]; Gomes, Leonardo Q. [UNESP]; Damato, Tatiana M. M. [UNESP]; Mota, Jorge; Werneck, André O.; Christofaro, Diego G. D. [UNESP] (Wiley, 2021)
Physical activity has been associated with enhanced mental health among adults. However, it is not clear in the literature which domains (occupational, transport and leisure-time exercise) and intensities (moderate, vigorous and moderate-to-vigorous) of activity provide the greatest benefits. The aim of the present study was to describe the association of different domains and intensities of physical activity with depressive symptoms in adults. This was a cross-sectional observational study conducted among 209 adults (≥18 years) in Brazil. Depressive symptoms were assessed using the HADS questionnaire (Hospital Anxiety and Depression Scale). Physical activity intensities (moderate, vigorous and moderate-to-vigorous) were device-measured by accelerometry. Physical activity in different domains (occupational, transport, and leisure-time exercise) was self-reported using a questionnaire. Chronological age, ethnicity, body mass index, highest academic achievement, employment status, alcohol consumption, tobacco smoking, chronic morbidity and soft-drink ingestion were adopted as adjustment confounding factors. Linear regression analysis revealed that total self-reported physical activity [β = –0.100 (95%CI: –0.180 to –0.019)] and leisure-time exercise [β = –0.311 (95%CI: –0.468 to –0.155)] were negatively associated with depressive symptoms, but only leisure-time exercise remained significant after adjustment for confounding factors [β = –0.243 (95%CI: –0.409 to –0.076)]. Thus, leisure-time exercise was cross-sectionally associated with lower depressive symptoms in community-dwelling adults. Highlights Leisure-time physical activity was the only physical activity domain associated with lower depressive symptoms. This association appears to be independent of potential confounders. Potential interventions should focus on leisure-time domain.
Keywords: accelerometer; depression; domains; intensity; Physical activity